(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the role of modern political parties in the development of small business and entrepreneurship in Uzbekistan. It analyzes the influence of political parties on economic reforms, their legislative initiatives, and their efforts to create a favorable business environment. The study highlights key challenges, such as the lack of institutionalized mechanisms for direct collaboration between political parties and entrepreneurs. Comparative analysis with developed countries reveals the need for systematic engagement and policy enhancements. The article concludes with recommendations for strengthening political parties’ role in supporting entrepreneurship, fostering sustainable economic growth, and improving business-friendly policies.